GE_GERICHTE PS/39/2020 vom 8. März 2022 - GE Cour de justice (2022)
POLICE;MESURE DE CONTRAINTE(PROCÉDURE PÉNALE);FOUILLE DE PERSONNES;VIRUS(MALADIE);VOL(DROIT PÉNAL) | CPP.197; CPP.217; CPP.249; CPP.251; CPP.431